Effect of CTMABr/SiO2 molar ratio in synthesis of micro-mesoporous ZSM-5 composite and its application in 5-EMF (biofuel additive) formation - Manal, Prajakta N.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Bokade, Vijay V. (Environmental Progress and Sustainable Energy, 2024)
Synthesis of micro-mesoporous zeolite composite with optimum micro and mesoporosity is an emerging research area due to its wide applications, especially in bulk chemical or biomass transformations. It offers advantages in preserving zeolite crystallinity, creating mesoporosity and converting bulky molecules into valuable products. This work presents the process of preparing bimodal micro-mesoporous ZSM-5 using dual templates (CTMABr and TPABr). XRD, N2 adsorption-desorption, SEM, TEM, Si-29, and Al-27 NMR were used to analyze the two-dimensional micro-mesoporous ZSM-5. One-step synthesis of bimodal micro-mesoporous ZSM-5 features dual micro/mesoporosity by a marginal decrease in the crystallinity (71%). Micro-mesoporous ZSM-5 composite was found to be dependent on the optimum CTMABr/SiO2 molar ratio of 0.04 to 0.06. The micro-mesoporous ZSM-5 zeolite composite was evaluated for cascade synthesis of 5-EMF (methoxymethyl furfural- biofuel additive) from fructose and exhibited a five fold increase in 5-EMF yield to 24.2% as compared with parent ZSM-5 (4.6%).
Keywords: fructose; methoxymethyl furfural-biofuel additive; micro-meso composite; ZSM-5